Development of Realistic and Real Time Virtual Mirror Application for Electronic Cosmetic System - TSUMURA, Norimichi; MIYAKE, Yoich; KINOSHITA, Hayato; NAKAGUCHI, Toshiya; MAKINO, Takao (Journal of The Society of Photographic Science and Technology of Japan, 2008)
We present a virtual mirror system for tracking a 3D position and orientation of a user's head in real-time with a single video camera. The “virtual mirror” is a system that can reproduce a mirror image of user's face onto the display by using a video camera and a half mirror. Unlike a normal mirror, virtual mirror can enlarge the facial image or change the facial color. Our goal is to create the electronic cosmetic system with the virtual mirror. To achieve our goal, we proposed the real-time face tracking method with one video camera. This method can track the facial movement and expression separately by using a multistep particle filtering and a facial database.